Knowledge, attitude and practice of obstetricians towards external cephalic version - Moon, Aisha; Shabbir, Saima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Breech presentation is found in 3-5% of pregnant women at term. The cause for this fetal presentation may vary from fetal to maternal. Management option for breech presentation includes assisted vaginal breech birth, caesarean section and external cephalic version. External cephalic version is a maneuver performed to avoid breech presentation at term labor and helping the obstetricians to avoid complications of cesarean section. The success rate of ECV is 50%. Considering a high success rate and low risks it can be concluded that ECV can help reduce cesarean section rate of any region. The objective of this study is to determine the knowledge, attitude and practice of healthcare practitioners towards external cephalic version. Methods: This is an observational cross-sectional study conducted by the postgraduate trainee of Kulsumbai Valika social security SITE hospital, Karachi, Pakistan. By purposive sampling selection, there were 50 consultant obstetricians that have been well informed and were willing to complete KAP study questionnaires were enrolled to participate. Results: A total of 50 participants were included, 70% had clinical experience of more than 10 years. 80% considered ECV a safe procedure.75% believe that effective knowledge and practice of ECV can bring down cesarean section rate. If encountered by client with breech presentation 69% will manage with elective LSCS (lower segment caesarean section), 26% with ECV and only 5% will manage with assisted breech vaginal birth. Conclusions: For uncomplicated singleton breech at term, both ACOG and RCOG recommend external cephalic version. In Pakistan the current trend involves performing cesarean section for breech presentation. Effective knowledge, Proper training, and adequate practice can improve ECV uptake in our country.